Identity, hybridity and cultural home Chinese migrants and diaspora in multicultural societies - Liu, Shuang 1959- (London Rowman & Littlefield International, 2015)
"Explores identity formation and cultural home for generations of Chinese immigrants living in multicultural societies across the world"--Publisher.
Introduction : where is the cultural home in a multicultural society? -- Chinese migrants and diaspora -- Culture and cultural home -- Acculturation and adaptation -- Hybridity and intercultural identity -- Identity negotiation and reconstruction -- Intercultural marriage and interracial children -- Biculturalism and multiculturalism -- Conclusion : do we need a cultural home in a multicultural society?
Includes bibliographical references (pages 187-202) and index.
Keywords: Chinese diaspora; Chinese -- Ethnic identity. -- Foreign countries; Multiculturalism